Seven replies to the critiques of Modern Money Theory - Éric Tymoigne (Levy Economics Institute of Bard College, 2021)
Modern Money Theory (MMT) has generated considerable scrutiny and discussions over the past decade. While it has gained some acceptance in the financial sector and among some politicians, it has come under strong criticisms from all sides of the academic spectrum and from conservative political circles. MMT has been argued to be both fascist and communist, orthodox and heterodox, dangerous and benign, unworkable and obvious, and unrealistic and clearly nothing new. The contradictory aspects of the range of criticisms suggest that there is at best a superficial understanding of the MMT framework. MMT relies on a well-established theoretical framework and is not inherently about changing the economic system; it is about changing the policymaking praxis to implement a given public purpose. That public purpose can be small or large and can be conservative or progressive; it ought not to be narrowly determined but rather should be set as democratically as possible. While MMT proponents tend to favor a public purpose that deals with what they see as major drawbacks of capitalist economies (persistent nonfrictional unemployment, unfair inequalities, and financial instability), their policy proposals do not lead to a major shift of domestic resources to the public purpose. If a major increase in government spending is implemented, MMT provides some guidance on how to do that in the least disruptive manner by drawing on past economic experiences. The point is to implement the public purpose at a pace that recognizes the potential constraint that comes from domestic resource availability and potential inflationary pressures from bottlenecks, rising import prices, and exchange rate depreciation, among others. In most cases, economies have more flexibility than what is admitted. In all cases, when monetary sovereignty prevails, the fiscal position and the public debt are poor metrics for judging the viability of a public purpose and its pace of implementation. As such, applying MMT to policymaking does not mean that a government ought to be encouraged to record fiscal deficits or that the relation between the central bank and the treasury ought to be radically changed to allow direct financing. The fiscal balance is not a proper policy goal because it leads to irrelevant or incorrect policymaking and because it is largely outside the control of policymakers. The financial praxis of monetarily sovereign governments already conforms to MMT. Central banks and treasuries routinely coordinate their financial operations. Some governments have allowed direct financing of the treasury by the central bank; others have not but have developed equivalent ways to coordinate their fiscal and monetary operations that work around existing political constraints. Such routine coordination ensures an elastic financing of government operations that at least deals with domestic resources and is not intrinsically inflationary.
Keywords: B52; E12; E31; E32; E42; E51; E52; E61; O1; O4; 330; Modern Money Theory (MMT); Post-Keynesian Economics; Inflation; Economic Growth; Public Finance; Policymaking; Public Debt; Fiscal Deficit; Fiscal Policy; Monetary Policy